Nilal Tunal Anultas Naik dan Anuitas Turun Dengan Mempertimbangkan Tingkat Inflasi Konstan - Gamal, M. D. H.; Sitompul, Dewi Utami; Kho, Johannes (Jurnal Pilar Sains, 2006)
Given an interest rate i and an inflation rate j, both are constant and not equal to zero for n periods. For twocases I > j and i < j , we can obtain the geometrically varying annuity and real cash flow present valuesfrom the increasing and decreasing immediate annuities.